Comparative Assessment of the Mineral Content of a Latin American Raw Sausage Made by Traditional or Non-Traditional Processes - González-Tenorio, Roberto; Fernández-Diez, Ana; Caro, Irma; Mateo, Javier (IntechOpen, 2012)
None